The Effect of Work Environment, Motivation, and Leadership on Employee Performance with Employee Engagement as Mediating Variable - Glisina Dwinoor Rembulan; Hu Limei; Filscha Nurprihatin (JIEMS (Journal of Industrial Engineering and Management Systems), 2021)
Performance appraisal is a major factor in company development, so companies can assess the level of achievement of the vision and mission, business performance appraisal, manager appraisal, cross-departmental assessment, and assessment of all employees in the company. This assessment is intended to predict the company's future expectations. The purpose of this study is to analyze and determine which factors affect employee performance in the workplace. This research is conducted at one of the construction services companies where the number of skilled employees continues to decrease, and the company has experienced a decline in achievement of Key Performance Indicators (KPI) from 2015 to 2018. The analysis technique used in this study uses the Structural Equation Modeling method. (SEM) with the help of SmartPLS (Partial Least Square) software. The results of the analysis show that the work environment variable (X1) has a positive and significant relationship to the employee engagement variable (Y1) and has a positive but not significant effect on the Employee Performance variable (Y2), the motivation variable (X2) has a positive and a significant influence on the employee engagement variable (Y1) and employee performance (Y2). The leadership variable (X3) has a positive but not significant effect on the employee engagement variable (Y1) and has a positive but not significant effect on the employee performance variable (Y2). The employee engagement variable (Y1) as a mediating variable has a positive and significant effect on the employee performance variable (Y2). The results also show that the employee engagement variable has a simultaneous influence of 56.8% which can be explained by the variables of work environment, motivation, and leadership. Employee performance variables have a simultaneous effect of 60.5% which can be explained by the variables of work environment, motivation, leadership, and employee engagement.